PERAN LITERASI KESEHATAN MENTAL, LOKUS KONTROL, DAN GENDER TERHADAP SIKAP MENCARI BANTUAN PROFESIONAL PSIKOLOGI PADA MAHASISWA - I Dewa Ayu Srideswari Putri; Ni Made Ari Wilani (Universitas Negeri Padang, 2022)
As an undergraduate student, individuals are faced with various challenges and risk to experience psychological problems. The positive attitude toward seeking professional psychological help is needed by students to have a tendency to seek rather than refuse professional help so that they can solve psychological problems that have been experienced. Individual attitudes toward seeking professional help are influenced by several factors such as mental health literacy, locus of control, and gender. This study is aimed to determine the role of mental health literacy, locus of control, and gender toward attitudes to seek professional psychological help on undergraduate students in Bali. This study was conducted using a quantitative survey method with the research subjects were 318 undergraduate students at universities in Bali aged 18-25 years and domiciled in Bali. The results of the multiple regression test showed that there were roles of mental health literacy, locus of control, and gender in increasing the attitudes toward seeking professional psychological help (F=24,040; p=0,000<0,05). Mental health literacy, locus of control, and gender also partially played a role in increasing attitudes toward seeking professional psychological help (mental health literacy: t=5,749, p=0,000; internal locus of control: t=4,147, p=0,000; external locus of control: t=2,236, p=0,026; gender: t=3,222, p=0,001). The implication of this research is to provide consideration for issues that prevent students from seeking professional psychological help.